Doing Business and Role of Government for Entrepreneurship Development - Karki, Bir Bahadur (Journal of Nepalese Business Studies, 2012)
Doing business takes perspective of domestic primarily smaller companies and measure the regulation applying to them through their life cycle. The objective is regulation designed to be efficient accessible to all and simple in their implementation. Globally, doing business remain easiest in OECD high income economies. Out of 183 economies Singapore retains to top ranking or the ease of doing business whereas Nepal has ranked in 116. The main aims of one village one product (OVOP) and one Tambon one product (OTOP) is to develop micro, small and medium enterprise at the grass root level and reduce unemployment problems and poverty alleviation. These programme are more or less based on public private partnership (PPP) policy and technique. Like, other country, Nepal has been adopted OVOP programme within 11 districts out of 75 districts, since 2006. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page :53-62 Uploaded date: July 8, 2012